Estudio del nivel de presión sonora y su incidencia en las otopatías ocupacionales en la planta de hormigón Guayllabamba de la Compañía Herdoíza Crespo Construcciones S.A. Propuesta de un sistema de prevención de ruido. - Saltos Echeverría, Jorge Geovanny (2015)
This research makes a noise study in Concrete Guayllabamba Company Herdoiza Crespo Constructions S.A. in order to develop a Noise Prevention System. First we identify the presence of Occupational Ear pathology in workers with greater exposure to industrial noise using labor audiometry. Then identify Risk Factors most affected using qualitative matrix that considers the probability and consequence. To encourage this investigation a study of sound pressure level in terms of work in Concrete Company is performed. The study uses the engineering method UNE-EN ISO 9612: 2009 containing all jobs exposure. These trials included the determination of the level of SPL equivalent in 1/1 octave band according to the corresponding show and then determine the dose and the expanded level uncertainty with a confidence level of 95%. The hypothesis tested in this study is that noise affects Occupational Ear pathology for the execution of work in the Concrete Company. The deep of industrial noise determined that the risk factor partially intolerable for this system of work was the noise. The Noise Prevention System product of this work identified some control measures to the aspects set as high risk in terms of source controls in the middle and at the receiver.